Basophils control T cell priming through soluble mediators rather than antigen presentation - Möbs, Christian; Salheiser, Martin; Bleise, Fabian; Witt, Marie; Mayer, Johannes U. (Frontiers in Immunology, 2023)
Basophils play an important role in the development of T helper type 2 immunity and have been linked to protective immunity against parasites but also inflammatory responses in allergic diseases. While typically classified as de-granulating effector cells, different modes of cellular activation have been identified, which together with the observation that different populations of basophils exist in the context of disease, suggest a multifunctional role. In this review we aim highlight the role of basophils in the context of type 2 immunity and focus on the contribution basophils play in the context of antigen presentation and T cell priming. We will discuss evidence that suggests that basophils perform a direct role in antigen presentation and relate it to findings that indicate cellular cooperation with professional antigen-presenting cells, such as dendritic cells. We will also discuss tissue-specific differences in basophil phenotypes that might lead to distinct roles in cellular cooperation and how these distinct interactions might influence immunological and clinical outcomes of disease. This review thus aims to consolidate the seemingly conflicting literature on the involvement of basophils in antigen presentation and tries to find a conclusion to the discussion if basophils influence antigen presentation through direct or indirect mechanisms.